A dulce de leche-like product with the lipid profile of pecan oil - Ranalli, Natalia (2017)
Dulce de leche (DL), a concentrated sweetened milk product, is highly consumed in Latin America and exported to other countries, such as USA and Spain. DL is traditionally prepared by concentrating 3% w/v fat milk with sucrose and vanilla until ~70% total soluble solids is reached, obtaining a minimum fat content of 6% w/w. As DL is the most-consumed sweet spread in Argentina, particularly by children, it was an obvious candidate for substitution with respect to saturated fats.